(untitled) (Ágora de Heterodoxias, 2024)
The objective of this essay is to reflect on systemic organizational analysis in an uncertain, complex and transdisciplinary reality, which ranges from talking about “planetarization” in the 90s (Morín) to an emerging deglobalization according to the last World Economic Forum in Davos (2023). Morín’s paradigm combines with Fayol’s classical vision, Neilson and Paternack’s organizational DNA theory, Chiavenato’s systematics and Carrasco’s perspective; interpret that effectively in a “planetary” environment with emerging signs of deglobalization, in the presence of complex and unpredictable social phenomena, change and uncertainty are normal, and therefore the analysis of organizations corresponds to an open and unpredictable systems perspective, where the manager must adapt to this chaotic, disruptive and accelerated normality, generating security in their decisions, so that organizational objectives can be achieved, avoiding falling into poor work organization. Through a reflective methodology, and with a theoretical panorama based on 4 authors, it is concluded that the organization in an environment of disruptive challenges, can fulfill its objectives efficiently, maintaining the unity Man (subject)-Organization (object) and their complex relationship as the sum of the whole